ABOUT THE PROJECT "SMART-STUDY RUSSIAN AS A FOREIGN LANGUAGE IN THE CONTEXT OF THE DEVELOPMENT OF THE DIGITAL EDUCATIONAL SPACE IN A NON-LINGUISTIC ENVIRONMENT" - Malikova, Anna; Fatkieva, Gulnara; Gladkova, Ekaterina; Keldeshova, Olga (Pedagogy and Psychology, 2021)
The introduction of educational distance services into the training system is of urgent importance at the present time. This article presents a web platform for foreign students studying Russian (levels A1, A2). The methodology, approaches and methods of teaching Russian as a foreign language are listed. The obtained practical experience shows that learning through the use of digital technologies allows integrating educational technologies and increasing its effectiveness in synchronous and asynchronous learning. The research is based on the existing models in linguistic science, but at the same time its specificity and approach have no analogues in Kazakh science. The appearance of such a website will allow foreigners to improve their basic writing, speaking, reading and listening skills under the guidance of a teacher and independently. The use of digital services in the classroom contributes to the presentation of the material in a more accessible, visual form, which will help to improve the quality of memorization and academic performance in a mixed learning format.